MicroRNA-9 Inhibits NLRP3 Inflammasome Activation in Human Atherosclerosis Inflammation Cell Models through the JAK1/STAT Signaling Pathway - Yue Wang; Zhihua Han; Yuqi Fan; Junfeng Zhang; Kan Chen; Lin Gao; Huasu Zeng; Jiatian Cao; Changqian Wang (Cellular Physiology and Biochemistry, 2017)
Background/Aims: MicroRNA-9 (miR-9) is involved in inflammatory reaction in atherosclerosis; however, its function and regulatory mechanisms remain unclear. We aimed to uncover the exact roles of miR-9 and downstream signaling pathways using in vitro human atherosclerosis models. Methods: We used oxidized low-density lipoprotein (oxLDL)-stimulated human THP-1 derived macrophages, oxLDL-stimulated human primary peripheral blood monocytes and lipopolysaccharides (LPS) or Alum-stimulated human THP-1 derived macrophages as in vitro atherosclerosis inflammation models. Transient transfection of over-expression vectors, small interference RNAs (siRNAs) or antisense oligonucleotides was used to regulate intracellular protein or miR-9 levels. Cell responses and signal transduction were detected by multiple assays including Western blotting, enzyme-linked immunosorbent assay (ELISA) and luciferase reporter assay. Results: MiR-9 inhibited while anti-miR-9 antisense oligonucleotides induced interleukin-1 beta (IL-1β) and NLRP3 inflammasome activation in all in vitro models. Janus kinase 1 (JAK1) and matrix metalloproteinase 13 (MMP-13) were identified as the target genes of miR-9. In oxLDL-stimulated human THP-1 derived macrophages, knockdown of JAK1 by siRNA blocked the phosphorylation of signal transducer and activator of transcription 1 (STAT1) and mimicked the effects of miR-9. In the same model, JAK1 knockdown blocked the phosphorylation of NF-κB p65 in the nuclei and the phosphorylation of NF-κB IκBα in the cytoplasm. Conclusions: Our study demonstrated that miR-9 could inhibit activation of the NLRP3 inflammasome and attenuate atherosclerosis-related inflammation, likely through the JAK1/STAT1 signaling pathway. Therefore, miR-9 may serve as a potential therapeutic target for atherosclerosis.